Accent Assessment: A Preliminary Study of Scaling Validity - McDaniel, D. Mike; Neeley, Richard A.; Isaacson, Julie J.; Howard, G. Daniel (Journal of International Students, 2012)
Direct Magnitude Estimations (DME) and Equal Appearing Interval (EAI) scaling techniques were used to compare listeners’ perceptions of the extent of accent from recorded speech samples of international students enrolled in a United States university who spoke English as a second language. Twenty five international students served as speakers by reading the same brief passage for recording purposes. Twenty five American-born students with no formal training or experience with accents or accent reduction rated the extent of the accent on each of the spoken samples using both scaling techniques. Statistical analysis of the listener’s perceptions indicated no significant differences between the DME or EAI scaling procedures and a scatterplot comparing the data sets for each technique produced a significant linear relationship between the data for the two techniques.